Spatial Effects of Logistics Infrastructure on Interregional Growth in Indonesia - Dhieva Leona Febriant; Wahyu Widodo (Universitas Negeri Semarang, 2026)
This study aims to analyze the impact of logistics infrastructure, physical capital growth, human capital, and population growth on interregional economic growth in Indonesia from 2014 to 2023, and to evaluate the presence of interregional spillover effects. The analysis uses panel data of 34 provinces with a Spatial Durbin Model (SDM) under a fixed effect approach. The results indicate that the effect of logistics infrastructure varies across types and regions: road length consistently shows a positive and significant effect, whereas airports and seaports tend to have negative effects, especially in Eastern Indonesia. The land transport (trucks) contributes positively, though significance varies across regions. Spatial analysis indicates heterogeneous spillover effects: roads generate positive spillovers, while airports, seaports, and truck may produce negative spillovers in certain regions. Physical capital has a relatively small and insignificant direct effect, whereas human capital shows positive and significant effects, particularly in Eastern Indonesia. Population growth has a directly negative effect in Eastern Indonesia, but total effects can be positive through labor mobility and interregional market integration. These findings highlight the importance of improving the quality and efficiency of logistics infrastructure, spatially based development planning, and affirmative policies to support more equitable economic growth